2010
DOI: 10.1161/circresaha.110.227371
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of FoxO by Sirt1 Plays an Essential Role in Mediating Starvation-Induced Autophagy in Cardiac Myocytes

Abstract: Rationale: Autophagy, a bulk degradation process of cytosolic proteins and organelles, is protective during nutrient starvation in cardiomyocytes (CMs). However, the underlying signaling mechanism mediating autophagy is not well understood. Objective:We investigated the role of FoxOs and its posttranslational modification in mediating starvationinduced autophagy. Methods and Results:Glucose deprivation (GD) increased autophagic flux in cultured CMs, as evidenced by increased mRFP-GFP-LC3 puncta and decreases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
527
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 603 publications
(570 citation statements)
references
References 23 publications
(40 reference statements)
22
527
4
Order By: Relevance
“…Among the sirtuin family, both SIRT1 and SIRT6 are localized in the nucleus and share functional similarity in terms of antisenescence as relates to extending life span. Although SIRT1 induces autophagy for regulation of longevity in case of caloric restriction (30)(31)(32), reduced SIRT1 expression by CS exposure has been implicated in increased autophagy activation in COPD pathogenesis through enhanced apoptosis (11). Therefore, decreased expression levels of both SIRT1 and SIRT6 2) and SIRT6 cDNA (lanes 3, 4) transfected HBECs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the sirtuin family, both SIRT1 and SIRT6 are localized in the nucleus and share functional similarity in terms of antisenescence as relates to extending life span. Although SIRT1 induces autophagy for regulation of longevity in case of caloric restriction (30)(31)(32), reduced SIRT1 expression by CS exposure has been implicated in increased autophagy activation in COPD pathogenesis through enhanced apoptosis (11). Therefore, decreased expression levels of both SIRT1 and SIRT6 2) and SIRT6 cDNA (lanes 3, 4) transfected HBECs.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Therefore, we investigated the effects of starvation on protein acetylation levels by immunofluorescence staining of permeabilized and fixed leukocytes with an antibody specific for protein containing acetylated lysine residues. Cytofluorometric analyses revealed that starvation caused a significant reduction in the levels of protein acetylation in circulating white blood cells from mice ( Fig.…”
Section: Alterations In Protein Acetylation After Starvationmentioning
confidence: 99%
“…Since fasting stimulates myocardial autophagy, [11][12][13]16 we evaluated cardiomyocyte autophagosome abundance in male mice carrying cardiomyocyte autophagy reporter GFP-tagged MAP1LC3B (green fluorescent protein-tagged microtubule-associated protein 1 light chain 3) transgene 13 subjected to intermittent (qOD) fasting for 6 wk (on a fed day). Mice subjected to 24 and 48 h of fasting, or to 24 h of fasting followed by 24 h of refeeding to mimic a fasting-refeeding cycle; and nonfasted agematched controls were studied in parallel.…”
Section: Fasting-refeeding Cycles Modulate Myocardial Autophagymentioning
confidence: 99%
“…27 We examined the effects of partial loss of LAMP2 on autophagy in the myocardium, which is a critical lysosomal pathway stimulated in response to starvation, 11,14,15 and is impaired in mice with complete loss of LAMP2. 28 Female Lamp2 heterozygous null mice (bearing the X/null genotype at the Lamp2 locus), demonstrate no difference in body weight or heart weight ( Table 1) as compared with littermate wild-type females.…”
Section: Fasting-refeeding Cycles Modulate Myocardial Autophagymentioning
confidence: 99%
See 1 more Smart Citation